Assessing the impact of infrastructure investments using customs data: The case of the greater Mekong Subregion corridor and the People's Republic of China - Yesim Elhan-Kayalar; Konstantin Kucheryavyy; Manabu Nose; Yasuyuki Sawada; Ruo Shangguan (Asian Development Bank (ADB), 2023)
This paper provides new evidence of the effects of road construction on both domestic and international trade flows in the People's Republic of China (PRC) using customs data and information on transport investments in the region, including those supported by multilateral development banks. We find that road construction helped to reduce trade costs significantly from 2000 to 2011, supporting the catch-up of inland regions in the PRC to its coastal cities. The ad valorem rate of internal trade costs decreases by 20%, and the ad valorem rate of international trade costs decreases, on average, by 15.3%, with substantial heterogeneity of effects across sectors. Using satellite and customs data, we also document that the construction of the Kunming-Bangkok Expressway led to local economic growth and higher regional specialization in accordance with comparative advantage, suggesting the role of the road construction in facilitating market integration across borders in the Greater Mekong Subregion.
Keywords: R40; R41; F10; F13; 330; development impact; infrastructure; economic growth; trade; job creation; regional specialization; market integration